Species-Specific Deamidation of RIG-I Reveals Collaborative Action between Viral and Cellular Deamidases in HSV-1 Lytic Replication - Huichao Huang (American Society for Microbiology, 2021)
Herpesviruses are ubiquitous pathogens in human and establish lifelong persistence despite host immunity. The ability to evade host immune response is pivotal for viral persistence and pathogenesis.